Texas Gains on NAEP: Points of Light? - Camilli, Gregory (Education Policy Analysis Archives, 2000)
The 1992-1996 gain in mathematics scores on NAEP from 4th to 8th grades in Texas is placed in perspective. The "miracle" in Texas looks much like the median elsewhere. Of 35 states and two districts (Guam and D.C.), the 52-point gain of Texas was good enough to earn Texas a rank of 17th or about the 46th percentile. Taking into consideration the wealth of states, Texas stands in the middle of the packno worse than most other states in delivering educational services to students.